1986
DOI: 10.1021/bi00355a012
|View full text |Cite
|
Sign up to set email alerts
|

N-hydroxysulfosuccinimido active esters and the L-(+)-lactate transport protein in rabbit erythrocytes

Abstract: Esters of N-hydroxysulfosuccinimide strongly inhibit L-(+)-lactate transport in rabbit erythrocytes, probably by acylating amino groups on the transport protein. Lactate transport studies using bis(sulfosuccinimido) suberate (BS3), bis(sulfosuccinimido) adipate (BS2A), bis(sulfosuccinimido) dithiobis(propionate), and a variety of monocarboxylate esters suggest that an exofacial amino group of the lactate transport protein is essential for lactate transport. Also, reductive methylation studies show that even wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Furthermore, our own data reveal that although the conservative replacement of Arg 306 with lysine allows for expression at the plasma membrane (Figure 6), the protein is catalytically inactive (Supplementary data Table II). This is a similar situation to that found in lactate dehydrogenase where arginine is critical for substrate binding (Hart et al 1987) and like lactate dehydrogenase, MCT1 is inhibited by the arginine-specific agent, phenylglyoxal (Donovan & Jennings 1986, Poole & Halestrap 1993). …”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, our own data reveal that although the conservative replacement of Arg 306 with lysine allows for expression at the plasma membrane (Figure 6), the protein is catalytically inactive (Supplementary data Table II). This is a similar situation to that found in lactate dehydrogenase where arginine is critical for substrate binding (Hart et al 1987) and like lactate dehydrogenase, MCT1 is inhibited by the arginine-specific agent, phenylglyoxal (Donovan & Jennings 1986, Poole & Halestrap 1993). …”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, in the case of rat and rabbit red blood cells, rates of lactate transport were found to be very rapid and to display conventional Michaelis-Menten kinetics indicative of the presence of a single MCT [8,9]. As such, these cells were an ideal starting material for identifying the protein responsible for transport, and several groups used a variety of covalent labelling techniques in their attempts to accomplish this [10][11][12][13]. Unequivocal identification was ultimately achieved in our laboratory using covalent labelling of the protein with 4,4h-di-isothio-cyanatostilbene-2,2h-disulphonate (DIDS) ; labelling was prevented by specific inhibitors of the transporter such as α-cyano-4hydroxycinnamate (CHC).…”
Section: Identification Cloning and Sequencing Of Mct1mentioning
confidence: 99%
“…A positively charged group that binds the carboxylate anion is a feature that is likely to be present in all MCTs. In red-blood-cell MCT1 arginine probably fulfils this role, since the argininespecific reagent phenyglyoxal inhibits MCT1-mediated lactate transport [2,12,67]. This is also the case in lactate dehydrogenase [68].…”
Section: Structure-function Relationships In the Mct Familymentioning
confidence: 99%
“…Jennings & Adams-Lackey (1982) found that incubation of rabbit erythrocytes with [3H]4,4'di-isothiocyanodihydrostilbene-2,2'-disulphonate ([3H]H2DIDS) labelled a membrane protein of 40-50 kDa on SDS/PAGE, in parallel with inhibition of lactate transport. Other reagents which, like H2DIDS, are capable of reacting with exofacial amino groups, afforded protection against labelling of this band by [3H]H2DIDS (Donovan & Jennings, 1985, 1986. However, this evidence for the identity of the transporter is circumstantial, and attempts to label a similar protein in rat erythrocytes, which have a similarly active monocarboxylate transporter to those from rabbit, have met with failure (see ).…”
Section: Introductionmentioning
confidence: 99%